Post-Sovereign and Subaltern Diplomacy: A Postcolonialism Comparative Analysis of Papua, Catalonia, and Kurdistan - Setyaka, Virtuous (Papua Journal of Diplomacy and International Relations, 2025)
This article examines the dynamics of non-state diplomacy practiced by subaltern communities in postcolonial contexts. Using a comparative study of Papua, Catalonia, and Kurdistan, it explores how these communities leverage diaspora networks and digital diplomacy to gain international support, resist state hegemony, and challenge the global order that disproportionately favors state sovereignty. Employing a postcolonial framework, the article analyzes how subaltern groups use social media, transnational forums, and diaspora networks to create symbolic resistance and push back against dominant political narratives. The study is based on secondary data, including reports from international organizations, media publications, and digital activity analyses. The article argues that while subaltern diplomatic strategies have gained effectiveness, especially through the use of social media and the mobilization of diasporas, substantial obstacles remain in achieving wider international recognition. These challenges largely stem from the entrenched dominance of powerful states and an international system that prioritizes state sovereignty over subaltern claims. KEYWORDS   Catalonia; Papua; Kurdistan; Post- Sovereign; Subaltern Diplomacy